Topology Optimization of Electrolyte-Electrode Interfaces of Solid Oxide Fuel Cells based on the Adjoint Method. Issue 13 (1st January 2019) - Onishi, Junya; Kametani, Yukinori; Hasegawa, Yosuke; Shikazono, Naoki
Abstract : Topology optimization is conducted to find the optimal meso-scale structure for the electrolyte-anode interfaces of solid oxide fuel cells. In the present optimization method, the total reaction current in the anode is chosen as an objective function to be maximized. The adjoint method is applied to compute the sensitivity of the objective function with respect to the interface shape, which is considered as the design variable. A cylindrical pillar structure is used as an initial guess and is iteratively modified according to the optimization procedure. From the optimization results, it is shown that the optimal structure has multiple branches at the top side and characteristic sub-structures like wrinkles at the bottom side. In addition, the geometrical analysis of the optimal structure shows that the wrinkles contribute to the performance by homogenizing the electrochemical potential.